SOSIALISASI ANCAMAN DAN MANFAAT PENGGUNAAN MEDIA DIGITAL UNTUK SISWA MENENGAH ATAS SEDERAJAT DITINJAU DARI IT ETHIC, REGULATION AND CYBER LAW - Ranggi Praharaningtyas Aji; Albana, Ilham (Nusantara Hasana Journal, 2024)
Using the concept of an independent learning curriculum for students at Miftahul Huda Rawalo Vocational School to express themselves and create digitally. Therefore, the digital work of Miftahul Huda Rawalo Vocational School students needs to be ensured in accordance with ethical and legal principles. It is important to instill knowledge about IT ethics, digital world rules and Indonesian cyber law in these students. With this problem, it is necessary to provide direction and explanation regarding applicable ethics and law, both formal and digital ethics and law. The AMM team will explain matters related to IT ethics and cyber law in attractive and digitalized packaging so that it is easy fors participants to understand and understand. The result of this activity is that students know the issues regulated by IT ethics related to the ITE Law and regulations related to content and digital media created by students. Know the limits of what is and is not allowed in digital media. And awareness of the importance of maintaining digital content created by students in the field of ethics and IT regulations.